The origin of enhanced optical absorption of the BiFeO3/ZnO heterojunction in the visible and terahertz regions. Issue 40 (25th September 2015) - Feng, Hong-Jian; Yang, Kang; Deng, Wan; Li, Mengmeng; Wang, Mingzi; Duan, Bi; Liu, Feng; Tian, Jinshou; Guo, Xiaohui
Abstract : The separation of photoinduced carriers makes the BiFeO3 /ZnO heterostructure a promising candidate for BiFeO3 -based ferroelectric photovoltaic cells. Abstract : Optical absorption is improved for the BiFeO3 /ZnO heterostructure prepared by a sol–gel process, especially, in the terahertz energy region. A dipole-corrected slab model is used to describe the bilayer film, and first-principles calculations agree with the experiments which present unambiguous explanation for the enhancement of the optical properties. Two-dimensional electrons in the ZnO side of the heterostructure are found to play an essential role in forming the photoinduced carriers and the enhancement of the absorption. The conducting layers tend to penetrate into the interface and decrease the band gap, leading to the transport of carriers through the interface to the BiFeO3 side. The photoinduced carriers can be separated by the ferroelectric domains in BiFeO3, and this mechanism makes the heterostructure an ideal candidate for BiFeO3 -based ferroelectric photovoltaic cells.